2006
DOI: 10.1007/s11010-006-9178-7
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides induced oxidative stress in thymocytes

Abstract: The role of oxidative stress in immune cell toxicity caused by the pesticides lindane, malathion and permethrin was investigated in thymic cells from C57BL/6 mice. Thymocytes treated with any of these pesticides (concentrations ranging between 50-150 microM) were found to generate both superoxide ((*)O(2) (-)) and H(2)O(2). The production of (*)O(2) (-) was detected with hydroethidine-ethidium bromide assay. H(2)O(2) production was monitored with a flow cytometric fluorescent (DCFH-DA) assay. All three pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…), the hepatotoxicity induced by this chemical is mainly due to a potentiation of oxidative stress [44]. Another study performed on C57/BL6 mice confirmed that the toxicity of lindane in thymocytes is explained by an enhancement of O 2 -and hydrogen peroxyde [45]. These paradoxical effects could be explained by greater doses of lindane and chlordecone used by these authors.…”
Section: Discussionmentioning
confidence: 86%
“…), the hepatotoxicity induced by this chemical is mainly due to a potentiation of oxidative stress [44]. Another study performed on C57/BL6 mice confirmed that the toxicity of lindane in thymocytes is explained by an enhancement of O 2 -and hydrogen peroxyde [45]. These paradoxical effects could be explained by greater doses of lindane and chlordecone used by these authors.…”
Section: Discussionmentioning
confidence: 86%
“…de Liz Oliveira Cavalli [146] found that exposure to glyphosate causes oxidative stress and activates multiple stress-response pathways leading to Sertoli cell death in prepubertal rat testis. The role of oxidative stress in immune cell toxicity induced by the pesticides lindane, malathion, and permethrin was examined by Olgun and Misra [147]. Hassoun et al [148] reported that chlordane produces oxidative tissue damage based on the levels of hepatic lipid peroxidation and DNA damage (Table 3).…”
Section: Purposementioning
confidence: 99%
“…Rout and Shaw (2001) reported that SOD forms the first step in the removal of ROS; it rapidly removes O 2 -, and hence decreases the risk of the formation of OH from O 2 -. Esterase inhibition due to profenofos was also reported in larvae of Trichoplusiani ni and Bemisia tabaci (Olgun and Misra 2006). Lindane, Malathion, and Permethrin were known to increase total SOD activity in thymic cells from C57BL/6 rats (Panamangalore and Bebe 2000).…”
Section: Discussionmentioning
confidence: 79%